Gamification-Based Mobile Learning in Elementary School Learning : Literature Study - ANIK TWININGSIH ANIK TWIn (SEAMEO SEAMOLEC, 2025)
This study aims to examine the implementation of gamification-based mobile learning as a learning medium in elementary schools. The method used is a literature study by analyzing various previous studies related to the concept, benefits, and challenges of implementing this technology-based learning media. The results of the study indicate that gamification-based mobile learning can increase students' learning motivation, develop high-level thinking skills, and provide a flexible and inclusive learning environment. This learning media is designed through stages that include making flowcharts, storyboards, interface development, and product evaluation. Gamification, as a key element, utilizes features such as points, levels, and badges to create an interactive and engaging learning experience. Although it offers various advantages, such as high accessibility and personalization of teaching materials, its implementation requires adequate infrastructure support and curriculum adaptation. With the right design, gamification-based mobile learning can be an innovative solution to improve the quality of learning in elementary schools.